2020
DOI: 10.13057/asianjfor/r00300204
|View full text |Cite
|
Sign up to set email alerts
|

Bee flora resources and honey production calendar of Gera Forest in Ethiopia

Abstract: Abstract. Bareke T, Addi A. 2019. Bee flora resources and honey production calendar of Gera Forest in Ethiopia. Asian J For 3: 69-74. Gera forest contains substantial coverage of natural forest and known as a Key Biodiversity Hotspot area for Coffea arabica conservation and one of the potential areas for beekeeping. The study was carried out to assess the bee flora and flowering calendar to harvest more honey following the flowering plant cycle. Semi-structured questionnaires, participatory Rural Appraisal (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 3 publications
4
21
2
Order By: Relevance
“…Honeybees ( Apis mellifera L.) obtain nectar and pollen from flowering plants (Bareke & Addi, 2019a ). The availability of bee flora is the most important factor that can influence the activities of honeybees and their production (Keasar & Shmida, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Honeybees ( Apis mellifera L.) obtain nectar and pollen from flowering plants (Bareke & Addi, 2019a ). The availability of bee flora is the most important factor that can influence the activities of honeybees and their production (Keasar & Shmida, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Schefflera abyssinica was a secondary pollen source (41.38 %) in the Gera district of Jimma Zones and Didu (42.38%) district of I/A/Bora. Schefflera abyssinica is an abundant bee forage plant in moist highlands of southwestern and southeastern parts of Ethiopia and it provides monofloral honey in these areas[29]. Degaga[30] also reported that Schefflera abyssinica is a major monofloral honey source tree in Gera District, Jimma Zone.…”
Section: Resultsmentioning
confidence: 99%
“…The area has high humidity and is rich in fauna and flora biodiversity. Three study districts (Goma, Gera, and Shebe Sombo) were selected based on ecosystem differences and beekeeping potential (Bareke and Addi 2019).…”
Section: Study Area Profilementioning
confidence: 99%